2012
DOI: 10.1590/s0100-204x2012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Grazing intensities and poultry litter fertilization levels on corn and black oat yield

Abstract: -The objective of this work was to assess the effect of poultry litter fertilization levels on corn and black oat yield using different grazing intensities, poultry litter levels (mixture of manure and bedding material) and a chemical fertilization level. The experimental design was a randomized complete block in a split-plot arrangement with four replicates. Black oat + ryegrass grazing intensities, characterized by different pasture sward management, with animal entrance at 25, 30 and 35-cm heights and exit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Despite the superiority of mineral fertilization, there was a residual effect of application of compost from one crop to the next. Adami et al (2012), in a study on fertilization with poultry litter, also found a residual effect on yield of black oat in succession with corn.…”
Section: Resultsmentioning
confidence: 93%
“…Despite the superiority of mineral fertilization, there was a residual effect of application of compost from one crop to the next. Adami et al (2012), in a study on fertilization with poultry litter, also found a residual effect on yield of black oat in succession with corn.…”
Section: Resultsmentioning
confidence: 93%
“…We found no studies on the effects of associating poultry litter and Arad phosphate fertilizer over growth response and production of tropical forage grasses such as Urochloa brizantha and Panicum maximum. However, the positive effects of poultry litter on corn (Zea mays) and soybean (Glycine max) yields, as well as the effect of Arad phosphate on dry-matter production, have already been described (Adami et al, 2012;Orrico Júnior et al, 2013;Ragagnin et al, 2013). In this context, we tested the hypothesis that Arad phosphate fertilization associated with poultry litter would favor tropical forage grasses production and development, as well as P concentration in diagnostic leaves.…”
Section: Introductionmentioning
confidence: 97%
“…An alternative to enhance the benefits provided by the use of cover crops is also the use of organic waste as an alternative source of N in succession cropping. Considering the growth in the poultry sector and consequently this waste, it is necessary to use rational management techniques that minimize its impact on the environment, since poultry farming is an activity considered to have a high polluting potential (ADAMI et al, 2012). Poultry litter consists of a mixture of excrement with absorbent material from this poultry litter, in addition to feathers, shedding and feed remains from feeders (VIRTUOSO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%